Probability of Return of Spontaneous Circulation as a Function of Timing of Vasopressor Administration in Out-of-Hospital Cardiac Arrest. (2nd October 2015) - Hubble, Michael W.; Johnson, Christopher; Blackwelder, Jamie; Collopy, Kevin; Houston, Sara; Martin, Melisa; Wilkes, Delbert; Wiser, Jonina
Abstract: Introduction. Vasopressors (epinephrine and vasopressin) are associated with return of spontaneous circulation (ROSC). Recent retrospective studies reported a greater likelihood of ROSC when vasopressors were administered within the first 10 minutes of arrest. However, it is unlikely that the relationship between ROSC and the timing of vasopressor administration is a binary function (i.e., ≤10 vs. >10 minutes). More likely, this relationship is a function of time measured on a continuum, with diminishing effectiveness even within the first 10 minutes of arrest, and potentially, some lingering benefit beyond 10 minutes. However, this relationship remains undefined.Objective. To develop a model describing the likelihood of ROSC as a function of the call receipt to vasopressor interval (CRTVI) measured on a continuum.Methods. We conducted a retrospective study of cardiac arrest using the North Carolina Prehospital Care Reporting System (PREMIS). Inclusionary criteria were all adult patients suffering a witnessed, nontraumatic arrest during January–June 2012. Chi-square and t -tests were used to analyze the relationships between ROSC and CRTVI; patient age, race, and gender; endotracheal intubation (ETI); automated external defibrillator (AED) use; presenting cardiac rhythm; and bystander cardiopulmonary resuscitation (CPR). A multivariate logistic regression model calculated the odds ratio (OR) of ROSC as a function of CRTVI while controlling for potential confounding variables.Results. Of the 1, 122 patients meeting inclusion criteria, 542 (48.3%) experienced ROSC. ROSC was less likely with increasing CRTVI (OR = 0.96, p < 0.01). Compared to patients with shockable rhythms, patients with asystole (OR = 0.42, p < 0.01) and pulseless electrical activity (OR = 0.52, p < 0.01) were less likely to achieve ROSC. Males (OR = 0.64, p = 0.02) and patients receiving bystander CPR (OR = 0.42, p < 0.01) were less likely to attain ROSC, although emergency medical services response times were significantly longer among patients receiving bystander CPR. Race, age, ETI, and AED were not predictors of ROSC.Conclusions. We found that time to vasopressor administration is significantly associated with ROSC, and the odds of ROSC declines by 4% for every 1-minute delay between call receipt and vasopressor administration. These results support the notion of a time-dependent function of vasopressor effectiveness across the entire range of administration delays rather than just the first 10 minutes. Large, prospective studies are needed to determine the relationship between the timing of vasopressor administration and long-term outcomes.Keywords: Epinephrine, cardiac arrest, emergency medical services, paramedic, resuscitation, CPR